The benefits of endurance exercise and Tai Chi Chuan for the task-switching aspect of executive function in older adults: an ERP study - Fong, Dong-Yang; Chi, Li-Kang; Li, Fuzhong; Chang, Yu-Kai (Frontiers in Aging Neuroscience, 2014)
This study was designed to determine the relationship between physical activity and the task-switching aspect of executive function by investigating the modulating roles of age, modality of physical activity, and type of cognitive function using behavioral and event-related potential (ERP) assessments. Sixty-four participants were assigned to one of four groups based on age and history of physical activity: older adults performing endurance exercise (OEE), older adults practicing Tai Chi Chuan (OTC), older adults with a sedentary lifestyle (OSL), and young adults (YA). Study participants completed a task-switching task under homogeneous and heterogeneous conditions while ERPs were recorded. The results revealed that YA had shortest reaction times compared with the three older adults groups, with OSL exhibiting the longest reaction time. YA also exhibited shorter P3 latency than OSL. No differences were observed in P3 amplitude between YA, OEE, and OTC; however, all three groups had a significantly larger P3 amplitude compared with OSL in both task conditions. In conclusion, age and participation in physical activity influence the relationship between physical activity and task-switching, and a positive relationship was observed regardless of the modality of physical activity and type of cognitive function. Our ERP findings support the model of the scaffolding theory of aging and cognition and suggest that regular participation in endurance exercise and Tai Chi Chuan may have equivalent beneficial effects on cognition at the behavioral and neuroelectric levels.